Methodology for Teaching Students Professional Vocabulary of the Subject Area “Programming” - Mamalova K. E.; Alipkhanova F. N.; Kvitkovskaya A. A. (SHS Web of Conferences, 2023)
Today, the use of digital and Internet resources in education is practical and mobile for all participants in the educational process and is present not only in specialties that are mainly aimed at the world of digital and information technologies. The development of professional communicative competence of specialists in all industries (natural sciences, social, medical, political, legal) is possible with the use of resources for which representatives of the “Programming and Information Technology” sphere daily develop and improve existing programs, Database. In this work, we examined Internet resources from the standpoint of didactic utility in the framework of the educational process, highlighting their main functions: educational, communicative, developing, relaxation. We have determined that for the greatest possible efficiency when working with Internet resources, the teacher should take into account the presence of the presented didactic functions in the selected / developed resources. The specificity of teaching foreign language vocabulary in the subject area “Programming” lies in the close relationship between the disciplines of the professional cycle and foreign languages. This connection allows the teacher to motivate students to master vocabulary, grammatical structures of a non-native language through the presentation of professional topics, tools familiar in their native language, since the formation of a foreign language communicative competence of a professional is built taking into account the need to develop the ability to solve practically oriented tasks.